The Turkish-Kurdish Conflict in the Modern Globalized World - Ahlem Hamzaoui (The Journal of Studies in Language, Culture and Society, 2019)
The post-Cold-War era has reshaped the structure of international conflicts and their nature, especially after the breakup of the Soviet Union. In the modern globalised world, several driving mechanisms have had an impact on the nature of conflicts themselves. The 9/11 attacks, non-governmental organizations, international organizations, multinational companies, and even individuals are all main factors in changing conflicts’ nature around the world. This paper will shed light on the Turkish-Kurdish conflict. The Kurdish conflict in Turkey has been a prolonged affair. The year 1984 marked a new start for the contemporary emergence of the Kurdish problem on the Turkish political agenda. Since then the conflict has persisted in the form of guerrilla movements and limited warfare between Turkish government forces and the PKK (The Kurdish Workers' Party). Turkish- Kurdish conflict has dominated the world’s news landscape. Increasingly, Turkey has turned into an authoritarian state by suppressing critical voices and crushing an elected opposition party.  Over time, the political situation of Turkey’s Kurds has deteriorated into military confrontations between the Turkish central state and Kurdish nationalist groups.